PerLA: A thermo-hydro-mechanical framework coupling land–atmosphere interactions for evaluating highway and railway subgrade performance in permafrost regions - Jiaming Ye; Ruiqiang Bai; Weipeng Xu; Tianju Xue; Limin Zhang (Computers and Geotechnics, 2027)

Longitudinal association between metal mixture exposure and non-alcoholic fatty liver disease: A prospective cohort study based on generative adversarial networks - Jiaming Fu; Jinhao Jia; Honghui Li; Guojie Qiao; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; Xiaoyu Li; et al. (Environmental Pollution, 2026)

Sedimentary-diagenetic characteristics and genesis of the Upper Cambrian reservoirs in the Tabei area, Tarim Basin, NW China - Jun Li; Kaibo Shi; Bo Liu; Yongsheng Ma; Yuanchong Wang; Qing He; Jiaming Deng; Xichuan Men; Xiangyu Bai; Jianhao Hua (Journal of Asian Earth Sciences, 2026)

Unraveling the adverse outcome pathways of metabolic dysfunction-associated steatotic liver disease triggered by environmental mixtures via biological knowledge-driven machine learning - Jiaming Fu; Guojie Qiao; Kerong Ma; Jinhao Jia; Honghui Li; Zeyang Bai; Limeng Xiong; Yuhan Zhang; Xiaozhe Geng; Hongju Duan; Yuxi Wang; Chunqing Gao; et al. (Journal of Hazardous Materials, 2026)

Freeze–thaw cycles control successive glacier landslide hazards in Amney Machen Mountain - Jiaming Ye; Ruochen Jiang; Shihao Xiao; Yingyue Han; Luyu Ju; Wenjun Lu; Ruiqiang Bai; Tao Yao; Limin Zhang (Landslides, 2026)
Climate change has markedly increased the susceptibility of glacier-related landslides to alpine environments, leading to cascading processes with catastrophic impacts. Nevertheless, their triggering processes remain inadequately understood, which hinder robust hazard assessments and effective risk mitigation. Glacier collapses and cascading processes have been frequently observed at Xiaoma Gully in Amney Machen Mountain. Based on remote sensing, meteorological data analyses, field surveys and numerical simulations, glacier landslide hazard chains in this gully are reconstructed and associated triggers are identified. Results indicate that extreme diurnal freeze–thaw cycles drove the Xiaoma glacier collapses, and extreme temperature and precipitation accelerated glacier instabilities. The 365-day cumulative number of diurnal freeze–thaw cycles is identified as a critical precursor for initiating glacier collapses, serving as a quantitative indicator to characterize the long-term impact of freeze–thaw cycles. The application of this indicator to the Kolka Glacier collapse at Genaldon Valley in Russian Caucasus further demonstrates its feasibility. Furthermore, the catastrophic glacier landslide cascades underwent hazard-type transformation and displayed high mobility, reaching peak flow velocities over 30 m/s. This study sheds light on early warning and emergency management of glacier collapses in alpine regions.

Imidacloprid exposure at population-relevant doses induces hepatic lipid dysregulation: Exploring the role of cGAS-STING pathway-mediated hepatocyte senescence - Yuhan Zhang; Yuqing Dai; Yihong Di; Bing Wu; Xueyan Tian; Limeng Xiong; Zeyang Bai; Jinhao Jia; Jiaming Fu; Xiaoyu Li; Yi Zhao; Hao Hu; et al. (Environmental Research, 2026)

Longitudinal triglyceride-glucose index and Metal Interactions: A multi-model cohort integrating synergistic and antagonistic indices - Jinhao Jia; Yihong Di; Limeng Xiong; Buyun Liu; Zeyang Bai; Jiaming Fu; Yuhan Zhang; Xiaozhe Geng; Yuxi Wang; Chunqing Gao; Guojie Qiao; Hao Hu; et al. (Environmental Pollution, 2026)

Localized chemotherapy through metabolic stabilization and in situ gelation for ratio-locked delivery to maximize cytotoxicity and trigger immune responses - Jiaming Zhang; Xinyu Lou; Xiaolan Xu; Yingchao Li; Chenxia Bai; Qing Yan; Yanfang Wang; Yixiu Zhai; Jingdong Xiao; Mengchi Sun; Yinghou Wang; Jin Sun; et al. (Chemical Engineering Journal, 2026)

Co-pyrolysis mechanism of 1,1,1,2-tetrafluoroethane and soapstock: ReaxFF molecular dynamic and density functional theory study - Mengna Bai; Erguang Huo; Wei Zhuang; Jiaming Wang (Journal of Environmental Chemical Engineering, 2026)

Multifactorial synergistic strategies mediate the biocontrol of Fusarium oxysporum-induced root rot by Bacillus velezensis SYL-3 - He Liu; He Huang; Yuzhe Wang; Mengnan An; Jiaming Bai; Jianquan Zhou; Haiyang Lan; Aiwei Qi; Baoan Song; Yuanhua Wu (Pesticide Biochemistry and Physiology, 2026)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

Achieving fast Zn dynamics in high-mass-loading cathode via 3D-printed hierarchical graphene architectures in zinc-ion batteries - Shixiang Yu; Yongbiao Mu; Huicun Gu; Yonglin Zhang; Shuai Zhao; Haowen Liang; Bowen Hu; Jinxing Sun; Xiaoteng Chen; Lin Zeng; Jiaming Bai; Jinglei Yang (Chemical Engineering Journal, 2025)

Predictive biomarkers for valproic acid-induced hepatotoxicity in Chinese patients with epilepsy: the role of metabolites and genetic polymorphisms - Dingsheng Wen; Zhuojia Chen; Ziyi Chen; Xue Bai; Hongliang Li; Juan Chen; Qiling Dai; Guoping Zhong; Jiaming Qin; Guanzhong Ni; Min Huang; Liemin Zhou; et al. (Food and Chemical Toxicology, 2025)

Direct electrospinning of super fatigue resistant and fire-retardant aerogels for thermal insulation - Lingyun Wu; Jiaming Li; Yunfang Liu; Manxi Zhou; Dan Xue; Gang Bai; Aosong Zhou; Xiaoping Yang; Gang Sui (Chemical Engineering Journal, 2025)

Fe/Mo synergistic confinement in controlled N-doped carbon nanotubes frameworks: Multiscale insights and octogen degradation in multisolvent systems–performance, interfacial mechanisms, and electronic optimization - Junlan Tang; Jinmao Ma; Panpan Zhou; Jihui Zhang; Xiaojun Wang; Yuqian Shi; Jiaming Xu; Xiangru Zhou; Yuling Bai; Jiade Lin; Chi Chen; Lincheng Zhou; et al. (Chemical Engineering Journal, 2025)

Preparation of a smart nano-herbicide MP@HLDP with strong permeability performance improves herbicidal activity while reducing the adverse impacts - Xile Deng; Zeng Wang; Jiaming Yin; Zhichao Dong; Jie Shen; Shuo Yan; Lianyang Bai (Chemical Engineering Journal, 2025)

Acoustic micromixing in a serpentine channel with sharp teeth for controllable nanomaterial synthesis - Bin Ran; Bo Liu; Chaozhan Chen; Wenqiang Tong; Jiaming Shi; Jiaxi Du; Zhihang Yu; Siwei Bai; Huaying Chen; Yonggang Zhu (Chemical Engineering Journal, 2025)

Online sorting of surface defective walnuts based on deep learning - Jingwei Wang; Xiaopeng Bai; Daochun Xu; Wenbin Li; Siyuan Tong; Jiaming Zhang (Journal of Food Engineering, 2024)

Water and fertilizer decision model for synergistic optimization of yield, quality and efficiency of cherry tomato based on combination evaluation - Rui Li; Jiaming Bai; Dayong Li; Xinru Ren; Daiwei He; Rongcheng Du; Ziqi Feng; Zhi Zhang (Computers and Electronics in Agriculture, 2024)

Reduced moisture caused by short-term grazing prohibition results in a significant decrease of fungi abundance - Hongbin Zhao; Xiaofu Zhang; Huiyan Liu; Xue Bai; Jiaming Nie; Guodong Han; Bing Han (Journal of Arid Environments, 2024)

Thermal inactivation kinetics of Listeria monocytogenes in milk under isothermal and dynamic conditions - Xiang Wang; Jiaming Zheng; Linyin Luo; Yi Hong; Xiaofeng Li; Yuqi Zhu; Yufan Wu; Li Bai (Food Research International, 2024)

Effects of Dietary Lentinus edodes Fermentation Supplementation on Digestive Enzyme Activity, Antioxidant Capacity and Morphology of the Liver and Intestine in Largemouth Bass (Micropterus salmoides) Fed High Plant Protein Diets - Jiaming Xu; Zhoulin Yu; Guangye Liu; Sijie Li; Guoyong Zhou; Hanhua Wang; Yewei Dong; Cuihong You; Weidong Bai; Meng Zhou; Yanhua Huang; Xiaohong Tan (Fishes, 2023)
This study evaluated the effect of Lentinus edodes fermentation (LEF) on digestive enzyme activity, antioxidant capacity and morphology of the liver and intestine in largemouth bass (Micropterus salmoides) fed high plant protein diets (HPPD). LEF was supplemented in HPPD with 0 g kg−1 (LEF0), 10 g kg−1 (LEF1), 20 g kg−1 (LEF2), 30 g kg−1 (LEF3), 40 g kg−1 (LEF4), 50 g kg−1 (LEF5), respectively, and then the six diets were fed to largemouth bass with a body weight of 28.8 ± 0.05 g for eight weeks. Juvenile fish were randomized into 6 groups and each group had 4 replicates with 40 fish. Dietary LEF supplementation alleviated the liver inflammatory reaction of largemouth bass caused by HPPD and improved liver morphology. Goblet cells multiplied and the gut muscle layer thickened after LEF supplementation. The LEF significantly increased amylase activity in the liver and intestine of largemouth bass in individual experimental groups. The LEF could increase the activity of catalase in the liver and intestine of largemouth bass (p

Electron-transfer pathways insights into contaminants oxidized by Cu-OOSO3- intermediate: Effects of oxidation states of Cu and solution pH values - Lele Zhao; Jiaming Zhang; Zhiping Zhang; Yujun Zhu; Yuan Zong; Chengying Bai; Tong Wei; Yueming Ren; Jun Ma (Journal of Hazardous Materials, 2023)

Novel insights into Co synergy and electron-transfer pathways during the oxidation of contaminants by Cu-OOSO3- in CuCo2Ox/peroxymonosulfate system - Lele Zhao; Jiaming Zhang; Yuan Zong; Jun Ma; Chengying Bai; Hexin Zhang; Yueming Ren (Journal of Environmental Chemical Engineering, 2023)

Ultrasonic assisted preparation of ultrafine Pd supported on NiFe-layered double hydroxides for p-nitrophenol degradation - Xuan Zhou; Jiaming Shi; Xuefeng Bai (Environmental Science and Pollution Research, 2022)

Ultrasonic-assisted synthesis of highly stable RuPd bimetallic catalysts supported on MgAl-layered double hydroxide for N-ethylcarbazole hydrogenation - Xiaoran Liu; Jiaming Shi; Xuefeng Bai; Wei Wu (Environmental Science and Pollution Research, 2022)

HIV Tat Protein Induces Myocardial Fibrosis Through TGF-β1-CTGF Signaling Cascade: A Potential Mechanism of HIV Infection-Related Cardiac Manifestations - Yannan Jiang; Lu Chai; Hongguang Wang; Xiuyun Shen; Moyondafoluwa Blessing Fasae; Jinfeng Jiao; Yahan Yu; Jiaming Ju; Bing Liu; Yunlong Bai (Cardiovascular Toxicology, 2021)

Production of cyclic adenosine monophosphate by Arthrobacter sp. A302 using fed-batch fermentation with pH-shift control - Jiaming Cao; Xiaochun Chen; Huajing Ren; Jindan Zhang; Lei Li; Yong Chen; Jian Xiong; Jianxin Bai; Hanjie Ying (World Journal of Microbiology and Biotechnology, 2012)

Dynamic mathematical models of batch experiments and fed-batch cultures for cyclic adenosine monophosphate production by Arthrobacter A302 - Lei Li; Xiaochun Chen; Huajing Ren; Jiaming Cao; Jian Xiong; Jianxin Bai; Hanjie Ying (World Journal of Microbiology and Biotechnology, 2011)